KEANEKARAGAMAN TANAMAN PEKARANGAN DI DESA TAMBUSAI TIMUR KECAMATAN TAMBUSAI KABUPATEN ROKAN HULU PROVINSI RIAU - Yulianti, Devi; Purnama, Arief Anthonius; Brahmana, Eti Meirina (Sainstek : Jurnal Sains dan Teknologi, 2018)
This research purpose to know of wide diversity of the yard in the Village of Tambusai Timur District of  Tambusai Rokan Hulu Regency Province of Riau. This research have done on February until April 2018 that used direct observation (server inventarisasi). The plant that can be identify the researcher describ them with character of morfologyzal the source of reference the result of this research. Get the poin and indeksof wide diversity of the yard the telatively high on stasiun one (4,65), stasiun two (4,90) and stasiun three (3,72). That get 53 family, 96 genus and 107 species. The plant have habitus tree, shrub shaped or herbs that in use for ornamental plant, fruit and, food and medicine. All the species can get from the family Apocynaceae, Araceae, Euphorbiaceae, Myrtaceae, Palmae, Rutaceae and Zingeberaceae.